Intensification of inclusion body purification and protein refolding - Lee, Chew Tin (2003)
There is an increasing need to translate genomic information into commercial products through protein expression and production. Formation of the protein as solid inclusion bodies in E. coli is advantageous as it enables good initial purification, provided that acceptable refolding yields can be achieved. However, the recovery of active recombinant protein from complex biological mixtures via the route of IB-formation involves a series of complicated recovery steps, each of which can compromise the purity and yield of the desired product. Purification of IBs using traditional methods of homogenisation and centrifugation are difficult to automate for high-throughput applications, and are costly to scale. Process intensification by minimising the number of unit operations without a loss of product purity is desirable to improve yield and reduce production cost. Such a process should ideally be generic, scalable, easily automated to facilitate continuous processing, and should result in an improved refolding yield. Based on these criteria, an intensified unit operation termed an integrated Membrane Oscillatory Refolding (MOR) is introduced. The integrated MOR unit consists of an oscillatory flow reactor (OFR) that is integrated with a hollow ceramic membrane for cross-flow microfiltration operation. The key is the use of innovative chemical extraction technology in a non-solubilising mode for IB release, coupled with the MOR unit that acts as a novel microfiltration unit for IB purification and protein refolding. The technologies rely only on chemical reagents and on microfiltration that can be easily scaled and automated. The objective of this study is to establish and research the three key process steps essential to realise the integrated MOR unit: a non-solubilising chemical extraction method; a cross-flow microfiltration for IB recovery; and protein refolding via the hollow ceramic membrane in a novel reactor. Three of these process steps, validated using granulocyte macrophage-colony stimulating factor (GM-CSF) IBs, are successfully demonstrated and ready for integration into a single unit of MOR